Memproduksi kerajinan dari rumput laut / Rosmawaty Peranginangin, Ella sinurat, Muhammad Darmawan ; editor Th. Dwi Suryaningrum - PERANGINANGIN, Rosmawaty; Eliya Sinurat; Muhammad Darmawan; Dwi Suryaningrum, Th; Tri Murtini; Sony Nugroho (Penebar Swadaya, 2013)
76 hlm : ilus ; 23 cm [3 eks]